2013
DOI: 10.1007/s00223-013-9787-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Food Restriction Combined with Voluntary Running on Bone Morphology and Strength in Male Rats

Abstract: Athletes, in particular endurance athletes and dancers, are chronically exposed to a state of low energy availability due to insufficient dietary energy intake and massive exercise energy expenditure. Low energy availability sometimes causes bone fragility, thereby increasing the risk of bone disorders. Although the decrease in energy availability shows no sexual dimorphism, epidemiological studies have reported that bone disorders are less frequent in male athletes than in female athletes. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…In this study, low energy availability caused low BMD and microarchitectural deterioration in the growing male rats. In contrast, we revealed that the BMD and bone architecture had been little affected by low energy availability in mature male rats (19). Therefore, low energy availability is likely to greatly influence the bone tissue in growing male rats.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In this study, low energy availability caused low BMD and microarchitectural deterioration in the growing male rats. In contrast, we revealed that the BMD and bone architecture had been little affected by low energy availability in mature male rats (19). Therefore, low energy availability is likely to greatly influence the bone tissue in growing male rats.…”
Section: Discussionmentioning
confidence: 58%
“…However, few studies have examined the influence of a combination of food restriction and exercise training on bone strength and morphology using male animals (16), although many studies have examined either the effect of food restriction on bone tissue (15,17), or the effect of mechanical loading accompanied with physical activity on bone tissue (8,18). We reported that the BMD and the bone architecture had been little affected by food restriction combined with exercise training in mature male rats (19). However, it is unknown whether these phenomena are caused by the same conditions in the growing phase.…”
mentioning
confidence: 82%
“…Energy availability is defined as the difference between dietary energy intake and exercise-associated energy expenditure. Low energy availability, whether due to high energy expenditure or low dietary intake, is associated with altered bone turnover in both humans [57,58] and experimental animals [59][60][61]. Bone formation, in particular, is reduced under conditions of moderately low energy availability and bone resorption increases with extremely low energy availability [57].…”
Section: Discussionmentioning
confidence: 99%
“…In other rodent models (the ground squirrel and the chipmunk), it was reported that the tibia incurs significantly more stress than does the femur (Biewener 1983). In addition, the proximal tibia, a trabecular-rich region, is responsive to changes in load and is studied often (Iwamoto et al 2000;Sakakura et al 2001;Huang et al 2003;Iwamoto et al 2004;Hagihara et al 2005;Hattori et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Although there is controversy regarding the optimal type, duration, and intensity of exercise, impact activities (i.e., running and jumping) apply mechanical loading to weight-bearing bones and increase bone mineral mass, bone structure, and bone strength (Notomi et al 2000;Rizzoli et al 2010;Gomez-Cabello et al 2012). Benefits to bone health have been observed in young growing animal models (Raab et al 1990;Iwamoto et al 1999;Joo et al 2003;Wu et al 2004;Wallace et al 2007;Huang et al 2008), aging animal models (Beyer et al 1985;Raab et al 1990;Yeh et al 1993;Davicco et al 1999), and ovariectomized (Peng et al 1997;Sakakura et al 2001) and orchidectimized animal models (Horcajada et al 1997), as well as during food restriction in conjunction with voluntary wheel running (Hattori et al 2013). The "mechanostat" theory has been used widely to explain these changes in bone mass and architecture in response to functional loading.…”
Section: Introductionmentioning
confidence: 98%